PETA POSITIONING UANG ELEKTRONIK BERDASARKAN PERSEPSI MASYARAKAT DI INDONESIA TAHUN 2017 - Nisa Salsabila; Refi Rifaldi Giri (Jurnal Riset Bisnis dan Manajemen, 2017)
Background of this research is the apparance of electronic money in Indonesia which is subtitution of cash transaction. There are five objects that will be observed, they are Mandiri e-money, Flazz BCA, BRIZZI, cellular phone’s account, and Tapcash BNI. This research intends to give a representation of positioning maps about electronic money based on people’s perception who both use and do not use e-money in Indonesia 2017. Nonprobability sampling was used and the technique of analysis data is multidimensional scaling. The result of perception based on similliarity showed that Flazz BCA and Mandiri e-money, BRIZZI and Tapcash BNI were alike. However, it was not similar to cellular phone’s account. Result of perception by attributes showed that the user of e-money perceive that Mandiri e-money was the best amongst the others, while non-electronic money user claimed that Flazz BCA was the best.